Energy supply security in the European Union in the context of the gas conflict Ukrainian-Russian - Fernández, Ana; Rodríguez, Laura (Papeles de Europa, 2016)
This paper attempts to provide an overview of progress in the level of security of energy supply for gas in the Member States of the European Union (EU) to more purchases made this appeal to Russia. To do this we have constructed a synthetic indicator: the Weighted Index of Energy Security, which lets examine whether the degree of such security has declined in recent years as a result of the Russian-Ukrainian gas conflict occurred in 2006 and 2009. The results show that in most countries the opposite has happened.
Keywords: security of energy supply; gas; European Union; Russia; Ukraine